Economic cost and numerical evaluation of cooling of a cylindrical lithium-ion battery pack using air and phase change materials. (15th August 2022) - Tian, Man-Wen; Abed, Azher M.; Yan, Shu-Rong; Sajadi, S. Mohammad; Mahmoud, Mustafa Z.; Aybar, Hikmet Ş.; Smaisim, Ghassan Fadhil
Abstract: In this paper, the thermal management (THM) of a battery pack (BPK) with 9 cylindrical batteries is numerically modeled. The batteries are 18, 650 lithium-ion (LIN) type, which are placed in an air duct. A capsule of Phase Change Materials (PCM) is placed around all the LIN battery cells. The PCM used was CaCl2 .6H2 O, which was oval in the PCM capsule. This study was performed when the entire PCM was molten, and the air stream was trying to solidify it. At all times, the LIN battery is working and generating heat. By changing the horizontal distance of the battery cells from each other, this study has been done for different times of battery operation. An economic analysis has also been performed on the cost of electricity consumed to generate airflow in the battery pack for different battery distances. For numerical modeling, multi-physics COMSOL software has been used. The enthalpy method was used to simulate the PCM freezing front. Examination of the PCM solidification front showed that the PCM solidification was formed from the air inlet side. The highest amount of solid PCM occurred at fixed times for the first column of the LIN battery, while the last column batteries had the lowest amount of frozen PCM. Increasing the distance of the LIN battery cells horizontally from each other causes the amount of PCM temperature (T PCM ) and LIN battery temperature (T Bat ) to decrease. At 120 min and at a horizontal distance of 8 cm from each other, the amount of molten PCM is 22.98% and at a distance of 11 cm the amount of molten PCM It has reached 8.73%. Changing the distance between the batteries may thus affect the quantity of molten PCM by 14.25% at this time. It was also found that increasing the distance between the batteries reduces the cost of electricity used to solidify the PCM. Highlights: Thermal management of a battery pack with 9 cylindrical batteries is numerically modeled. A capsule of phase change materials is placed around all the lithium-ion battery cells. PCM solidification was formed from the air inlet side. Increasing distance of battery cells horizontally decreases PCM and battery temperatures.